Fragilidade financeira e vulnerabilidade externa na economia brasileira (1990-2013) - Peres, Samuel Costa (2014)
The main objective in this work is to examine the evolution of financial fragility and external vulnerability of the Brazilian economy from 1990s, i.e., from the country's deepening integration processes and financial liberalization. The central concern that motivates and justifies the study is that the way a country inserts itself internationally has different implications in terms of funding and dependence on foreign capital, and the ability to deal with external shocks or destabilizing factors, and, therefore, assumes a key role in the path of long-term growth of the economy. To cover the proposed objective, the study is divided into two interdependent essays. In the Essay 1, a literature review was conducted with regard to external financial fragility, taking as the starting point the financial instability hypothesis of Hyman Minsky. Afterwards, the index of external financial fragility (EFI) developed by Paula and Alves Junior (1999) is applied, in addition to a supplementary indicator, which served as the basis for the analysis. It was verified that the indicators of financial fragility reflected significantly the volatility and irregularity of foreign capital flows, even during periods of abundant international liquidity, demonstrating the financially unstable character of globalized economies. They also underlined the importance of foreign direct investment and long-term financing to reduce this fragility, and, especially, the necessity of a large volume of international reserves as an expansion of safety margins policy. The Essay 2 performed an analysis of the Brazilian external vulnerability in the referred period, focusing its structural character, through the examination of real-productive, technological, commercial and monetary-financial spheres, and a comparison of some newly industrialized countries (NICs), from structural external vulnerability index (EVI) proposed by Gonçalves (2005). Regarding the results, it became evident that the recurrent stocks and flows imbalances related to the international economic relations of the country indicate a high structural external vulnerability of the Brazilian economy. Furthermore, the international comparative analysis revealed that in the covered period, Brazil had the highest IVE between the economies of the group, while economies characterized by a more active and prudent insertion in the global market had the lowest rates. Finally, it can be concluded that the reduction of structural external vulnerability requires the capability of the Brazilian economy to rebalance its current account, making it less dependent on the financial account surpluses, i.e., less dependent on international liquidity cycles. Nevertheless, without the rescue of a development policy that promotes changes in the production structure, and produce reflexes on Brazilian exports, the only way to expand trade surpluses is the continued expansion of prices and international demand for primary and natural-resource intensive goods.